1995
DOI: 10.1063/1.359441
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth of AlN thin films on silicon (111) substrates by pulsed laser deposition

Abstract: Aluminum nitride thin films have been grown epitaxially on Si(111) substrates, for the first time, by pulsed laser ablation of sintered AlN target. The influence of process parameters such as laser energy density, substrate temperature, pulse repetition rate, nitrogen partial pressure, etc. on epitaxial growth has been investigated to obtain high quality AlN films. These films were characterized by Fourier transform infrared spectroscopy, Raman spectroscopy, x-ray diffraction (Θ and ω scans) technique, high re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(60 citation statements)
references
References 23 publications
2
58
0
Order By: Relevance
“…The strong peaks of the phonon modes indicate that the composition of the film is mainly AlN. Raman spectroscopy was carried out by Vispute et al [54,55] two spectra show the phonon mode with the frequencies in agreement with results reported above. These results clearly show that the laser deposited films contain pure AlN.…”
Section: Direct Pulsed Laser Ablation Excimer Lasersupporting
confidence: 76%
See 1 more Smart Citation
“…The strong peaks of the phonon modes indicate that the composition of the film is mainly AlN. Raman spectroscopy was carried out by Vispute et al [54,55] two spectra show the phonon mode with the frequencies in agreement with results reported above. These results clearly show that the laser deposited films contain pure AlN.…”
Section: Direct Pulsed Laser Ablation Excimer Lasersupporting
confidence: 76%
“…These results clearly show that the laser deposited films contain pure AlN. The AlN band-gap was measured from the optical absorption spectra and results to be 6.15 eV in agreement with that of crystalline AlN (6.2 eV) [42,55]. An Auger spectrum depth profile was obtained for an AlN film grown by laser ablation.…”
Section: Direct Pulsed Laser Ablation Excimer Lasermentioning
confidence: 62%
“…Extensive research is still necessary to find out exactly how the crystallographic structure and degree of crystallinity of AlN films depend on the film preparation method and conditions. Vispute et al reported the synthesis of h-AlN with (0001) orientation [6], while Zhu et al obtained cubic AlN films [8]. Metastable c-AlN was found in films synthesized by nitrogen-ion-assisted pulsed laser deposition [7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, AlN films deposited on Si are promising as microelectronic components thanks to their high dielectric constant and thermal conductivity, thermal and chemical stability, and good lattice match with SiC and GaN. However, obtaining AlN films with definite structure and crystalline quality still remains a challenge for most deposition techniques, such as metal organic chemical vapor deposition [1], reactive magnetron sputtering [2,3] and pulsed laser deposition (PLD) [4][5][6][7]. Extensive research is still necessary to find out exactly how the crystallographic structure and degree of crystallinity of AlN films depend on the film preparation method and conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The equipment used for Si surface preparation is shown in Figure 13 and included a wet bench, an automated spin rinse dry, and of course a monitored DI water supply. After implementing a standard wet clean procedure [25,26], defect free AlN films could be deposited. GaN epilayers were subsequently deposited with no evidence of melt back (Figure 14).…”
Section: Figure 11: Optical Image Of Gan On Pvd Aln Buffer Deposited mentioning
confidence: 99%